Exploring the perception of chemistry students at Kulliyyah of Science in learning organic chemistry - Rosly, Nurul Nadiah; A. Rahman, Nor Azlina; Abd Hamid, Shafida (IIUM Press, 2021)
Students perceive organic chemistry as a challenging subject for them to learn and master, which results in a high failure rate. This study investigates the perception of chemistry students of the Department of Chemistry, Kulliyyah of Science at International Islamic University Malaysia (IIUM), on organic chemistry courses and identify the topics that the students found difficult to grasp, which may affect their grades. The correlation of students’ perception on the difficulty level in studying organic chemistry subjects (I and II) with the grades obtained for both courses, and the correlation of the type of study attitude with the grades achieved for Organic Chemistry I and II, were also investigated. From the data analysis of questionnaires distributed to 160 respondents, stereochemistry (n = 58.8 %), determination of reaction type (n = 59.4 %), construction of the reaction mechanisms (n = 73.2 %), and characterisation of organic reaction (n = 77.5 %), were the topics that the students perceived to be difficult. Perception on the difficulty in studying organic chemistry was positively associated with the achievement of excellent grades for both organic chemistry subjects (I; rs = 0.413**, p<0.01 and II; rs = 0.436**, p<0.01). Quality of study attitude shows no association with the grades obtained for organic chemistry I (rs = 0.330**, p = 1.00) but positively associated with grades of organic chemistry II subject (rs = 0.140, p<0.01). This study could serve as a reference for lecturers to search for ways to design appropriate teaching approaches for better learning experiences